2010
DOI: 10.1002/chem.200902472
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Propargylic Amides: Mild Access to Oxazole Derivatives

Abstract: The substrate scope, the mechanistic aspects of the gold-catalyzed oxazole synthesis, and substrates with different aliphatic, aromatic, and functional groups in the side chain were investigated. Even molecules with several propargyl amide groups could easily be converted, delivering di- and trioxazoles with interesting optical properties. Furthermore, the scope of the gold(I)-catalyzed alkylidene synthesis was investigated. Further functionalizations of these isolable intermediates of the oxazole synthesis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(106 citation statements)
references
References 64 publications
5
99
0
2
Order By: Relevance
“…Interestingly, N‐propargyl carboxamides, which are well‐known for their facile cycloisomerization to oxazoles in the presence of gold catalysts,2, 23 form exclusively the gold vinyl 13 without cyclization. Less reactive internal alkynes such as 3‐hexyne also gave clean hydroauration products.…”
mentioning
confidence: 99%
“…Interestingly, N‐propargyl carboxamides, which are well‐known for their facile cycloisomerization to oxazoles in the presence of gold catalysts,2, 23 form exclusively the gold vinyl 13 without cyclization. Less reactive internal alkynes such as 3‐hexyne also gave clean hydroauration products.…”
mentioning
confidence: 99%
“…在较长的时期内, 金被认为是一种无 催化活性的惰性物质; 然而, 近 40 年以来, Au 催化剂的 诸多优点逐渐被发现且成为一个研究热点 [3] ; 与其它催 化剂相比, Au 催化剂具有独特优势, 其中金配合物催化 剂在 C-C、C-O 键生成反应、氧化和还原反应中就显 示了优异的催化性能 [4] , 尤其在分子间炔烃氧化方面备 受关注 [1e,5] . Hashmi 等 [4g,6] 报道了 Au(III)配合物催化体 系在五元杂环合成中显示了较高的催化活性. Zhang 等 [7] 利用 Au(I)配合物催化体系高效地合成了噁唑类化 167.39, 158.92, 133.92, 129.67, 128.77, 126.42, 112.60, 31.90, 31.72, 29.60, 29.58, 29.45, 29.32, 29.21, 22.67, 14.10;IR (neat) ν: 2924IR (neat) ν: , 2853IR (neat) ν: , 1516IR (neat) ν: , 1499IR (neat) ν: , 1461IR (neat) ν: , 1436IR (neat) ν: , 1245IR (neat) ν: , 1002 165.12, 157.36, 111.70, 31.90, 31.55, 29.59, 29.57, 29.43, 29.33, 29.31, 29.25, 22.67, 19.10, 14.10;IR (neat) ν: 2955IR (neat) ν: , 2924IR (neat) ν: , 2854IR (neat) ν: , 1524IR (neat) ν: , 1465IR (neat) ν: , 1376IR (neat) ν: , 1180IR (neat) ν: , 1131 156.79, 110.68, 44.81, 35.85, 31.89, 31.64, 29.58, 29.56, 29.42, 29.34, 29.31, 29.21, 27.99, 26.42, 22.66, 14.09;IR (neat) ν: 2924IR (neat) ν: , 2854IR (neat) ν: , 1522IR (neat) ν: , 1460IR (neat) ν: , 1377IR (neat) ν: , 1321IR (neat) ν: , 1130 8.28 (td,J=7.7,1.8 Hz,1H),7.36 (dddd,J=8.3,7.1,5.2,1.8 Hz,1H),7.26~7.21 (m,1H),7.17 (ddd,J=11.2,...…”
unclassified
“…18 Recently, Hashmi et al reported an elegant synthesis of halogenated oxazoles via the gold-catalyzed formation of alkylideneoxazolines (path e) 19 followed by the halogenation of them (path f). 18 Such a method have been extended to oxazole synthesis with the introduction of heteroatomic or carbon functional groups 20,21 as well as the further oxidation of iodinated alkylideneoxazolines (path g) 22 by Hashmi's and other groups. However, before our report on λ 3 -iodane-mediated oxidative cycloisomerization, 8 these two-step approaches to various functionalized oxazoles has been known.…”
Section: -Iodane-mediated Cycloisomerization/functionalization Reactionsmentioning
confidence: 99%